The spectacular evolution of Supernova 1996al over 15 yr: a low-energy explosion of a stripped massive star in a highly structured environment. Issue 3 (8th January 2016) - Benetti, S.; Chugai, N. N.; Utrobin, V. P.; Cappellaro, E.; Patat, F.; Pastorello, A.; Turatto, M.; Cupani, G.; Neuhäuser, R.; Caldwell, N.; Pignata, G.; Tomasella, L.
Abstract : Spectrophotometry of SN 1996al carried out throughout 15 yr is presented. The early photometry suggests that SN 1996al is a linear Type II supernova, with an absolute peak of M V ∼ −18.2 mag. Early spectra present broad asymmetric Balmer emissions, with superimposed narrow lines with P-Cygni profile, and He i features with asymmetric broad emission components. The analysis of the line profiles shows that the H and He broad components form in the same region of the ejecta. By day +142, the Hα profile dramatically changes: the narrow P-Cygni profile disappears, and the Hα is fitted by three emission components that will be detected over the remaining 15 yr of the supernova (SN) monitoring campaign. Instead, the He i emissions become progressively narrower and symmetric. A sudden increase in flux of all He i lines is observed between 300 and 600 d. Models show that the SN luminosity is sustained by the interaction of low-mass (∼1.15 M⊙ ) ejecta, expelled in a low kinetic energy (∼1.6 × 10 50 erg) explosion, with highly asymmetric circumstellar medium. The detection of Hα emission in pre-explosion archive images suggests that the progenitor was most likely a massive star (∼25 M⊙ ZAMS) that had lost a large fraction of its hydrogen envelope before explosion, and was hence embedded in a H-rich cocoon. The low-mass ejecta and modest kinetic energy of the explosion are explained with massive fallback of material into the compact remnant, a 7–8-M⊙ black hole.